ANALISIS RESEPSI BUDAYA POPULER KOREA DALAM VIDEO KLIP BLACKPINK DDU DU DDU DU PADA KOMUNITAS K-POPERS PEKANBARU - Ulfa Erfendy; Nita Rimayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Korean popular culture become a major phenomenon in various countries including Indonesia, which led to many communities formed by K-popers, including one community of K-popers Pekanbaru. K-popers as media audiences received a lot of Korean popular culture of the shows in the media. As one of them through a video clip Blackpink Ddu du ddu du are viral in Indonesia. K-popers watching video clips stretcher receives Korean popular culture in ways that may affect the extent of adopted Korean popular culture in everyday life. This research was aimed to determine the dominant reading, negotiated reading and opposional reading position of K-popers Pekanbaru to Korean populer culture in Blackpink’s Ddu du ddu du video clip.This research using descriptive qualitative research that focusing on the reception. The data was obtained through from interviews, observation and documentation with five informants who were selected using a purposive namely Annisa, Yola, Risma, Dilla and Donna. The data analysis technique used is the analysis method comprising reception of data collection, analysis and interpretation of data reception. Meanwhile, data validity checking techniques using triangulation.The first research result is the fifth informants dominant reception of K-pop music. The second is the informants who reception fashion and make up with negotiated. Third is there are no informants  who reception with opposition of video clip Blackpink’s Ddu du ddu du. The different in the way informants receptions Korean popular culture is due to several factors is age, educational, experience and culture can distinguish the way informants in reception of Korean popular culture. Keywords: Reception Analysis, Korean Popular Culture